(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Persistent pupillary membrane (PPM) is congenital developmental anomaly of mesodermal iris tissue. Purpose. To elaborate technology of microinvasive removal of obscurative pupillary membranes with intact anterior lens capsule preservation and lens transparency restoration. Material and methods. Surgical removal of obscurative PPM densely connected with anterior lens capsule was performed at three children 10,12 and 22 mo/o. Results. In all cases dense central PPM intimately connected with anterior lens capsule was separated and removed with keeping its integrity and without lens transparency breaking. The postoperative period proceeded without complications. Postop visual acuity improved to 0.2—0.4 and was nearly as in healthy eye. Conclusion. Delicate microinvasive removal of PPM intimately connected with anterior lens capsule allows to preserve lens transparency, to achieve stable visual improvement and high-grade rehabilitation of pediatric patients.